Legal Uncertainty in Testing of Legislation Due to Weak Implementation of the Principle of Lex Superior Derogat Legi Inferiori - Tanzill, Gistiana; Fitriah, Laelatul; Syamlina, Marha Awanis; Rosidin, Utang (Mahogany Journal De Social, 2026)
This study aims to examine the weak implementation of the principle of lex superior derogat legi inferiori and its implications for legal certainty within the Indonesian legal system. Using a normative juridical approach, the research applies statutory, conceptual, and case-based analysis to evaluate legislation and judicial decisions related to normative hierarchy. The findings reveal that the principle is not effectively operationalized due to systemic factors, including regulatory disharmony, procedural harmonization, overlapping judicial authority, low legislative quality, and formalistic administrative practices. These conditions result in persistent norm conflicts, delayed legal correction, and weakened predictability of legal outcomes. The novelty of this study lies in its integrative analytical framework that connects legislative processes, judicial review mechanisms, and administrative practices in explaining the failure of normative hierarchy. Unlike previous studies that focus primarily on doctrinal aspects, this research demonstrates that legal certainty depends on the interaction of multiple institutional dimensions. The study implies that strengthening preventive harmonization, improving legislative quality, and enhancing institutional coordination are essential to restoring the effectiveness of hierarchical principles. These findings contribute to the broader discourse on legal certainty, regulatory governance, and institutional reform in developing legal systems.